1995
DOI: 10.1074/jbc.270.33.19246
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration That Mammalian Methionine Synthases Are Predominantly Cobalamin-loaded

Abstract: Methionine synthase is an important cellular housekeeping enzyme and is dependent on the cofactor cobalamin, a derivative of vitamin B12, for activity. It functions in two major metabolic pathways including the tetrahydrofolate-dependent one-carbon cycle and the salvage pathway for methionine. Its dysfunction has several physiological ramifications and leads to the development of megaloblastic anemia. In addition, it is suspected to be involved in the pathogenesis of neural tube defects. An issue that is centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 22 publications
2
55
1
Order By: Relevance
“…Recent studies on purified Mtr and Cbs have shown reciprocal sensitivity of these two enzymes to oxidative conditions; Mtr is reduced (Chen et al, 1995) and Cbs is increased (Taoka et al, 1998) under oxidizing conditions. Thus, redox changes may serve a regulatory role such that oxidative stress would increase the flux of methionine through the transsulfuration pathway ultimately increasing the concentration of GSH .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on purified Mtr and Cbs have shown reciprocal sensitivity of these two enzymes to oxidative conditions; Mtr is reduced (Chen et al, 1995) and Cbs is increased (Taoka et al, 1998) under oxidizing conditions. Thus, redox changes may serve a regulatory role such that oxidative stress would increase the flux of methionine through the transsulfuration pathway ultimately increasing the concentration of GSH .…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of OHB,,, dithiothreitol is unable to transfer electrons to methionine synthase (21). The problem with this assay arises from its dependence on OHB,,, which serves both to transfer electrons from dithiothreitol to activate oxidized holoenzyme and binds to apoenzyme, eventually converting it to holoenzyme (12). Thus, the complexity of the methionine synthase assay has resulted in significant underestimation of the holoenzyme content in the literature.…”
Section: 5mentioning
confidence: 98%
“…This problem is addressed by employing titanium citrate as the electron donor since it can directly reduce methionine synthase (12). Under these assay conditions, the relative content of apo-and holoenzyme can be evaluated by measuring activity in the presence and absence of exogenous OHB,,.…”
Section: 5mentioning
confidence: 99%
“…Furthermore, as the sulfenate is at a low redox potential, Trx and DTT reduce it to restore its activity, but reduced glutathione does not affect the activity (13). Under oxidizing conditions, the cysteine pool is increased because of post-translational inhibition of methionine synthase (14,15) and post-translational activation of cystathione ␤-synthase (14,16). Inhibition of MST conserves cysteine and contributes to increase the cysteine pool.…”
mentioning
confidence: 99%